PENGARUH TEHNIK RELAKSASI BENSON TERHADAP PENURUNAN TINGKAT STRES LANSIA DI UNIT REHABILITAS SOSIAL WENING WARDOYO UNGARAN - Aryana, Kadek Oka; Novitasari, Dwi (Universitas Muhammadiyah Semarang, 2013)
Elderly stress is caused by physically, biologically, psychologically, and socially change. Beside of them, it is also affected by the condition of elders circumstance who lived in parlor. One of the ways to overcome the stress by non-pharmcologically is with Benson relaxation technique which is able to balance O2 in the brain. This research aims to know the influence of Benson relaxation technique to reduce stress level on elderly in Social rehabilitation Unit Wening Wardoyo Ungaran.The research design is quasi experimental design. The number of population in this research is 90 elders.While, the quantity of research sample is 30 respondents which are divided into 2 groups. Datas of elder’s stress level were collected by the usage of Depression Anxiety Stress Scale questionnaire. The univariate analysis was executed by monitoring the distribution of stress level frequencyat before and after the treatment and bivariate analysis was executed by the usage of paired t-test and unpaired t-test. The result shows that before Benson relaxation technique is applied towards intervened group, it is obtained that the average of respondents stress level is 22,93 (mid-level) SD (3,353). After Benson relaxation technique was applied, it is obtained that the average of respondents stress level was reducing at 18,33 (low-stress) SD (2,820). Benson relaxation technique shows significantly influence to reducestress level at p-value of 0,002 (p < 0,05). Based on the result, the technique can be applied as the stress treatment on elders in Social Rehabilitation Unit Wening Wardoyo Ungaran